Pengaruh Pengeluaran Pemerintah di Bidang Kesehatan dan Pengeluaran Pemerintah di Bidang Pendidikan terhadap Kemiskinan di Provinsi Kalimantan Selatan - Kinanti, Rinanda (PPJP ULM, 2018)
This study suggests government spending on education and health onpoverty in South Kalimantan Province in 2012-2016. Poverty is a significant andfundamental problem. Therefore, the purpose of this study looks at how the effects oreffects of education and health spending on poverty are affected. Panel data to beused in this research.The fixed-effect model (FEM) approach becomes the analytical method usedin this study using multiple linear regression analysis methods. And using theSimultaneous Test (Test F), Individual Test (Test t), and Test R-Square (R2).Based on the result of research estimation of expenditure or expenditurefrom the government of the field, education and health together have a significantinfluence on poverty, and the most dominant factor influencing poverty is governmentexpenditure in the health sector.